Dissecting the Biochemical and Transcriptomic Effects of a Locally Applied Heat Treatment on Developing Cabernet Sauvignon Grape Berries - Lecourieux, Fatma; Kappel, Christian; Pieri, Philippe; Charon, Justine; Pillet, Jérémy; Hilbert, Ghislaine; Renaud, Christel; Gomès, Eric; Delrot, Serge; Lecourieux, David (Frontiers in Plant Science, 2017)
Reproductive development of grapevine and berry composition are both strongly influenced by temperature. To date, the molecular mechanisms involved in grapevine berries response to high temperatures are poorly understood. Unlike recent data that addressed the effects on berry development of elevated temperatures applied at the whole plant level, the present work particularly focuses on the fruit responses triggered by direct exposure to heat treatment (HT). In the context of climate change, this work focusing on temperature effect at the microclimate level is of particular interest as it can help to better understand the consequences of leaf removal (a common viticultural practice) on berry development. HT (+ 8°C) was locally applied to clusters from Cabernet Sauvignon fruiting cuttings at three different developmental stages (middle green, véraison and middle ripening). Samples were collected 1, 7 and 14 days after treatment and used for metabolic and transcriptomic analyses. The results showed dramatic and specific biochemical and transcriptomic changes in heat exposed berries, depending on the developmental stage and the stress duration. When applied at the herbaceous stage, HT delayed the onset of véraison. Heating also strongly altered the berry concentration of amino acids and organic acids (e.g. phenylalanine, γ-aminobutyric acid and malate) and decreased the anthocyanin content at maturity. These physiological alterations could be partly explained by the deep remodelling of transcriptome in heated berries. More than 7000 genes were deregulated in at least one of the nine experimental conditions. The most affected processes belong to the categories “stress responses”, “protein metabolism” and “secondary metabolisms”, highlighting the intrinsic capacity of grape berries to perceive HT and to build adaptive responses. Additionally, important changes in processes related to “transport”, “hormone” and “cell wall” might contribute to the postponing of véraison. Finally, opposite effects depending on heating duration were observed for genes encoding enzymes of the general phenylpropanoid pathway, suggesting that the HT-induced decrease in anthocyanin content may result from a combination of transcript abundance and product degradation.